NETosing Neutrophils Activate Complement Both on Their Own NETs and Bacteria via Alternative and Non-alternative Pathways - Yuen, Joshua; Pluthero, Fred G.; Douda, David N.; Riedl, Magdalena; Cherry, Ahmed; Ulanova, Marina; Kahr, Walter H. A.; Palaniyar, Nades; Licht, Christoph (Frontiers in Immunology, 2016)
Neutrophils deposit antimicrobial proteins such as myeloperoxidase and proteases on chromatin, which they release as neutrophil extracellular traps (NETs). Neutrophils also carry key components of the complement alternative pathway (AP) such as properdin or complement factor P (CFP), complement factor B (CFB) and C3. However, the contribution of these complement components and complement activation during NET formation in the presence and absence of bacteria is poorly understood. We studied complement activation on NETs and a Gram-negative opportunistic bacterial pathogen Pseudomonas aeruginosa (PA01, PAKwt, PAKgfp). Here we show that anaphylatoxin C5a, formyl-Methionyl-Leucyl-Phenylalanine (fMLP), and phorbol myristate acetate (PMA) that activates NADPH oxidase induce the release of CFP, CFB and C3 from neutrophils. In response to PMA or P. aeruginosa, neutrophils secrete CFP, deposit it on NETs and bacteria, and induce the formation of terminal complement complexes (C5b-9). A blocking anti-CFP antibody inhibited AP-mediated but not non-AP-mediated complement activation on NETs and P. aeruginosa. Therefore, NET-mediated complement activation occurs via both AP- and non AP-based mechanisms, and AP-mediated complement activation during NETosis is dependent on CFP. These findings suggest that neutrophils could use their “AP tool kit” to readily activate complement on NETs and Gram-negative bacteria such as P. aeruginosa, whereas additional components present in the serum help to fix non-AP-mediated complement both on NETs and bacteria. This unique mechanism may play important roles in host defense, and help to explain specific roles of complement activation in NET-related diseases.